Urgensi Penguatan Kementerian Pelindungan Pekerja Migran Indonesia: Perbaikan Tata Kelola Lintas Sektoral Pelindungan Pekerja Migran Indonesia - Muhammad Zainuddin Akbar; Ivania Jaziel Christiani; Anang Setiyawan (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2025)
One of the major obstacles in the implementation of the Protection and Placement of Indonesian Migrant Workers (P2MI) lies in the suboptimal execution of cross-sectoral coordination. This is evidenced by the overlapping authorities between BP2MI, as the implementing agency, and the Ministry of Manpower (Kemnaker), as well as misinformation and data inconsistencies concerning migrant workers across ministries, institutions, and related agencies. This study aims to examine the various challenges in the cross-sectoral implementation of P2MI tasks. Using a normative legal research method and a statutory approach, this study identifies several key issues: (1) overlapping authority between the Ministry of Manpower and KP2MI/BP2MI, and (2) limited coordination among implementing ministries/agencies, particularly concerning the integration of migrant worker information systems. The study recommends that the government expedite the establishment of KP2MI and formally designate it as the central coordinator for P2MI tasks through a revision of the P2MI Law. Such a revision should be accompanied by the restructuring of the cross-sectoral implementation system and the harmonization of related implementing regulations